Agent of the imperium - Miller, Marc W. (Baen, 2021)
Jonathan Bland is a Decider, empowered by the Emperor himself to deal with the inevitable crises of an empire. In the service of the Empire, he has killed more people than anyone in the history of Humanity, to save a hundred times as many. He died centuries ago, but they reactivate his recorded personality whenever a new threat appears. When the crisis is over, they expect he will meekly return to oblivion. He has other ideas. The chronicle of Bland reveals secrets of the history of the star-spanning Third Imperium and spans 400 years from early Imperium (about year 300) through the mid-post Civil War period (about year 700) touching known and unknown events you may have encountered in your own reading of the Imperium: everyday events, political intrigue, deadly dangers, Arbellatra, Capital, Encyclopediopolis, the Karand's Palace, and a Tigress-class Dreadnought. If you know the Traveller science-fiction role-playing game, then some of this is already familiar; if not, no matter-this story introduces the vast human-dominated interstellar empire of the far future in ways only the designer and chronicler of this particular universe can.